Moral Values Representation through Speech Acts in Indonesian EFL Textbooks: A Critical Discourse Analysis - Harun Arwanto; Djatmika Djatmika; Nur Arifah Drajati; Kristian Adi Putra (JEELS (Journal of English Education and Linguistics Studies), 2024)
Abstract: In the last ten years, studies of the representation of moral values in English textbooks have been growing. However, little empirical evidence reveals the use of speech acts to represent moral values through utterances. This study aims to investigate the representation of moral values depicted through utterances in English textbooks for elementary school grades 2 and 5 in Indonesia. By adopting a socio-cognitive critical discourse analysis (Van Dijk, 2015) framework integrated with Searle’s (1969) speech acts, this qualitative study elucidates the representation of moral values only in the verbal text. The data were analyzed by applying several steps, including unitizing, sampling, recording/coding, reducing, inferring, and narrating. The findings of this study showed that curiosity, honesty, and friendliness are the most dominant moral values depicted in two English textbooks for elementary schools in Indonesia.  Dialogue/conversation, chapter cover, and instruction for students’ activity are the strategies to promote moral values in the textbooks. This study implies that teachers and textbook writers should provide students with more examples of moral values, particularly those related to daily life communication.